Two new ammonium/alkali-rare earth metal difluorophosphates ALa(PO2F2)4 (A = NH4 and K) with moderate birefringence and short cutoff edges. Issue 33 (10th August 2020) - Zhang, Wenyao; Wei, Zhonglei; Yang, Zhihua; Pan, Shilie
Abstract : ALa(PO2 F2 )4 (A = NH4 and K) are the first examples of ammonium/alkali-rare-earth metal difluorophosphates. The cutoff edge of KLa(PO2 F2 )4 is below 180 nm. The calculated birefringences are 0.023 and 0.019 for KLa(PO2 F2 )4 and NH4 La(PO2 F2 )4 . Abstract : Herein, two new ammonium/alkali-rare-earth metal fluorophosphates ALa(PO2 F2 )4 (A = NH4 and K) have been successfully obtained via a facile route. The introduction of F − anions with high electronegativity and non-π-conjugated species [PO2 F2 ] − was found in the title compounds. Different from the [PO4 ] 3− unit in phosphates, the (PO2 F2 ) − group retains the merit of wide UV transmittance in phosphates; meanwhile, it has large polarizability anisotropy, and theoretical calculation shows that the calculated birefringences are 0.023 and 0.019 for KLa(PO2 F2 )4 and NH4 La(PO2 F2 )4, respectively. More importantly, this work will contribute to the structural and functional diversity of phosphate chemistry by the exploration of the fascinating difluorophosphates.